Legal protection subject of research on health research in the field of dentistry education - Tahta Danifatis Sunnah; Endang wahyati Yustina; Irma H.Y Siregar (SOEPRA, 2019)
Medical education is an integrated education unit of scientific knowledge and clinical science. In its implementation medical education is inseparable from researches on health as requirements of students' academic graduation in medical and dental education programs students. The researches in medical and dentistry education are carried out by the students under the academic supervisors' guidance by the field of study. The researches include observational and experimental researches. In these two types of researches, the students are required to involve the research subjects, both experimental animals and human beings. In carrying out the researches it is necessary to get the permission of the subjects to be involved as the research subjects. This relates to the rights fulfillment and legal protection of the research subjects, especially in the field of dentistry education.This was a socio-legal study having analytically descriptive specifications. This study used primary and secondary data and the data gathering techniques were through field and literature studies. The data obtained were then qualitatively analyzed.The results of the study showed that the legal protection, both preventive and repressive, to the health research subjects in dentistry education had not yet been realized despite there had been legal provisions regulating it, among others, Act Nr. 20 of 2013 on Medical Education and the Regulation of the Minister Research, Technology, and Higher Education of the Republic of Indonesia Nr. 18 of 2018 on National Standards of Medical Education. Also, the arrangement form of the research subject's protection in any research conducted by the students of dentistry education was a Dean Decree outlined in academic guidelines on students' scientific papers. The decree included academic, ethical, and general requirements. In practice, the existing health research legal arrangements had not been effective except in evaluation monitoring. This was because some factors influenced the legal arrangement implementation of research subjects, namely juridical factor that was the fact that the regulations were not understood by the students; a technical factor that was lack of human resources; and social factor that was lack of socialization to the health research subjects.